A Study on Veterinary Faculty Students’ Opinions on Ethics Education and Career Choices: A Case of Ondokuz Mayıs University - Sefa Yıldırım; Berfin Melikoğlu Gölcü (Veterinary Medicine and Science)
ABSTRACT Background Veterinary ethics is a multifaceted element of the veterinary profession as it deals with various ethical issues related to medical practice, animal welfare, professional behaviour and societal expectations. By focusing on teaching ethics in veterinary medicine education, it will be possible to guide future veterinarians through the ethical dilemmas and conflicts they may encounter in their careers. Objectives To evaluate the opinions of the Ondokuz Mayıs University Faculty of Veterinary Medicine intern students about ethics education in veterinary medicine. Evaluation and comparison of the perspective on ethics education and career choice. Methods A cross‐sectional descriptive survey design was used to collect data via a questionnaire. Data obtained from 87 out of 119 students in the intern programme were evaluated. Responses were analysed by statistical methods. Results In the study, it was determined that pet veterinary services (private sector) and government veterinary services (public sector) were the leading career choices of intern veterinary students; female and male students wanted to turn to different fields of work; and the difference in career preferences did not change the views on ethics education. It was observed that students needed applied teaching and measurement‐evaluation methods in ethics education and sought role models in developing ethical attitudes and behaviours. In addition to gaining ethical knowledge in veterinary education, it was observed that they attach importance to professional and legal obligations. Conclusions This study is one of the few studies on veterinary ethics education and career choice in Turkey. The study results provide information to guide the development of veterinary ethics education to prepare future veterinarians for the complex ethical issues they will face in their careers.